ANALISIS PENGARUH PELATIHAN, PROMOSI, DAN KEPUASAN TERHADAP KINERJA PERAWAT DI RUMAH SAKIT PERMATA MEDIKA SEMARANG - Novian Subagyo, 0735020706 (Students Journal of Economic and Management, 2014)
This research study that tested the influence of training, promotion and job satisfaction of nurses in nurseâs performance in Permata Medika Hospital Semarang.This research has been fully tested on the respondents who work in the hospital as a nurse in Permata Medika Hospital Semarang, and hypothesis test using multiple regression test with the SPSS statistical tests.This research result explain that training, promotion and job satisfaction to employment and significant positive impact on the nurseâs performance. A variable whose most high influences the nurseâs performance is promotion based having the highest value on testing the regression coefficient.Keywords: training, promotion, and nurseâs job satisfaction